Are Substrate Types Factors Determining Tree Communities in Tropical Montane Cloud Forest? - Marco Antonio Espinoza-Guzmán; Diego Canales-Suardiaz; Julliana Barretto; Francisco Javier Sahagún-Sánchez (Forestist, 2024)
Tropical montane cloud forests (TMCF) are tropical vegetation that exhibits a great variety of specialized plant species due to the wide variation of abiotic factors, even along small distances. Climate, elevation, and other factors can also alter tree diversity and composition, such as geology, which was reported as the major determinant of differences between tree community structures growing in volcanic and limestone substrates. We assess how tree communities’ composition and diversity differ between fragments on limestone and volcanic substrates to corroborate a consistent spatial variation of forest composition and structure associated with geological substrates within tropical montane cloud forests. We registered 820 individuals of 64 species of temperate and tropical affinity. Sampling coverage was higher than 95%, and the most diverse indexes were registered to fragments on volcanic substrates. Four clusters were registered for species composition, with a high beta diversity and species turnover among sampled sites. The indicator species index varies between 0.54 to 0.88, being higher for Liquidambar styraciflua on volcanic substrate. Although substratum types can influence soil properties and determine differential species diversity, no evidence was found to corroborate that the tree community in tropical montane cloud forests is associated with a volcanic or limestone substrate. Tree community differences between and within sampled sites on volcanic and limestone substrates could be explained by the high species turnover due to the high tree heterogeneity of tropical montane cloud forests, forest recovery status, and disturbance.